HUMAN SECURITY IN THE SHADOW OF CONFLICT: ANALYSIS OF RISK AND MITIGATION STRATEGIES - Habibah, Siti Maizul; Setyowati, Raden Roro Nanik; Nufus, Ahmad Busrotun; Wahyudi, Wahyudi; Istianah, Anif (Jurnal Pertahanan dan Bela Negara, 2024)
Human security has become an important focus amidst the increasing global conflict that significantly impacts the lives of individuals and communities. Social, economic, and environmental instability caused by conflict threatens fundamental human rights, so a deep understanding of the potential for conflict and its mitigation strategies is essential. This study aims to analyze threats to human security in conflict and identify practical mitigation strategies. The methodology used is a literature review, which collects and analyzes various sources related to human security issues, potential for conflict, and mitigation strategies from publications between 2016 and 2020. The study results indicate that mitigating threats to human security requires a multi-dimensional approach. This includes inclusive economic development, preventive diplomacy to resolve tensions, strengthening state institutions to provide essential services and sustainable natural resource management. This study concludes that collaboration between local, national, and international actors is critical to achieving sustainable human security and preventing future conflicts. By integrating various approaches and ensuring the involvement of all parties, human security conditions can be improved, and potential conflicts can minimized.